Exploring Preschool Teachers' Pedagogical Content Knowledge: The Effect of Professional Experience - Ali Yigit Kutluca (Journal of Science Learning, 2021)
This study aimed to explore the pedagogical content knowledge (PCK) of preschool teachers. This multiple case study was conducted with the participation of two preschool teachers. In this way, two preschool teachers' PCK about science teaching was examined, and it was attempted to determine the underlying causes of their pedagogical conceptualizations about any subject. Therefore, the participants were asked to create a lesson plan specific to the subject matter they selected, answer the interview questions about PCK, and implement the lesson plan they created. While the participants' responses to the lesson plan and PCK interview questions were analyzed by inductive content analysis based on the constant comparative method, classroom observations were evaluated with an analytical evaluation rubric. Furthermore, PCK maps showing the interaction between the subject-specific and unique PCK components of preschool teachers were created. Results revealed that teachers did not have sufficient knowledge about science teaching and that their PCK tended to change according to professional experience. It was determined that experienced teachers had more teacher-centered orientations than less experienced teachers with more student-centered orientations. Moreover, it was observed that professional experience increased the relationship between the PCK components.